What's natural? Technoscience and the fear of cyborgs in sport - Guenter, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Since there are sporting competitions, there is also something like body enhancing technology. The use of performance-enhancing technical devices and supplements has a long history, stretching back to Ancient Greece and continuing within contemporary sport. While in the ancient world mostly dietary methods were used to improve performance, nowadays we deal with hormones, technical devices or even doped genes. `Human Enhancement` is a fascinating prism that reflects questions of participation, justice, equality and the autonomy of the subject in the social fields of sport. The area of elite sports is particularly affected by `human Enhancement`, according to the principle of exceeding what has come before, of aiming higher, faster and further. This paper analyses the postulated `naturalness` in the regulative and normalising function in the area of elite sports, in connection with Foucault`s theory of governmentality ant the methods of critical discourse analysis. Using different historical and current cases, the negotiating processes in relation to the argumentation logic, dynamics and resistance in shifting distinctions are presented using the fundamental documents of the IOC, IPC, CAS and IAAF. Represented through the inclusion and exclusion processes are hierarchies of the body that are (re)consolidated and transformed. The central question emerges as to how the worth of equal opportunity and fairness in regard to `naturalness` has been reconsolidated or/and transformed in the past and present.